Approximation properties by Schurer type q-Kantorovich–Stancu shifted knots operators - Abdullah Alotaibi (Journal of Inequalities and Applications, 2024)
Abstract We design the Schurer type Kantorovich–Stancu operators by using shifted knots in the quantum calculus. We obtain the convergence and other related approximation properties of these operators. We discuss the degree of convergence of our operators by applying the modulus of continuity. In addition, we give some basic direct theorems and obtain the approximation in Lipschitz spaces.